2011
DOI: 10.1002/prot.23136
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the successes and deficiencies of constant pH molecular dynamics: A blind prediction study

Abstract: A constant pH molecular dynamics method has been used in the blind prediction of pKa values of titratable residues in wild type and mutated structures of the Staphylococcal nuclease (SNase) protein. The predicted values have been subsequently compared to experimental values provided by the laboratory of García-Moreno. CpHMD performs well in predicting the pKa of solvent-exposed residues. For residues in the protein interior, the CpHMD method encounters some difficulties in reaching convergence and predicting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 49 publications
0
62
0
Order By: Relevance
“…Running simulations with different protonation states or constant-pH simulations are tools that can help to ameliorate these limitations. [83, 84]…”
Section: Exploration Of the Conformational Spacementioning
confidence: 99%
“…Running simulations with different protonation states or constant-pH simulations are tools that can help to ameliorate these limitations. [83, 84]…”
Section: Exploration Of the Conformational Spacementioning
confidence: 99%
“…In the first blind prediction exercise, the p K a values of 87 engineered mutants of staphylococcal nuclease (SNase) were calculated by many groups using both structure- and MD-based methods [36]. The accuracy of the GB-based DpHMD method was put to the test by McCammon and coworkers [37]. Based on the data of 11 residues from the engineered mutants as well as the wild-type variant of SNase, McCammon and coworkers concluded that while the accuracy of the DpHMD method for predicting the p K a ’s of surface sidechains is high (root-mean-square error of 1.2 units), challenge remains for interior and coupled sites which require increased sampling and accelerated convergence [37].…”
Section: Recent Applications Of Constant Ph Molecular Dynamicsmentioning
confidence: 99%
“…The accuracy of the GB-based DpHMD method was put to the test by McCammon and coworkers [37]. Based on the data of 11 residues from the engineered mutants as well as the wild-type variant of SNase, McCammon and coworkers concluded that while the accuracy of the DpHMD method for predicting the p K a ’s of surface sidechains is high (root-mean-square error of 1.2 units), challenge remains for interior and coupled sites which require increased sampling and accelerated convergence [37]. To address this issue, the Roitberg group and others applied the pH-REX protocol to revisit the p K a calculation of hen egg white lysozyme (HEWL) [19] and small peptides [38, 39].…”
Section: Recent Applications Of Constant Ph Molecular Dynamicsmentioning
confidence: 99%
“…In general, the inability of structure-based calculations to reproduce experimentally measured p K a values of internal groups stems from the failure to account correctly for structural reorganization (Karp et al, 2007). Several groups have made recent progress on this important problem (Arthur et al, 2011; Ghosh and Cui, 2008; Gunner et al, 2011; Kamerlin et al, 2009, Kato and Warshel, 2006; Meyer et al, 2011; Song, 2009; Wallace et al, 2011; Williams et al, 2011; Witham et al, 2011;Yoo and Cui, 2008; Zheng et al, 2008). To improve our understanding of determinants of p K a value of internal groups in proteins it is necessary to describe experimentally the character of the reorganization that is triggered by the ionization of internal groups.…”
mentioning
confidence: 99%